Percutaneous subtalar arthrodesis – configuration of portals using a guidewire - Feliciano Sarquis Dias, Paulo; Maciel, Bruno; Ferraz Ferreira, Gabriel; Schmidt, Eli; Alencar Mendes de Carvalho, Kepler; Araujo Nunes , Gustavo (Journal of the Foot & Ankle, 2023)
Subtalar arthrodesis is indicated to treat many hindfoot disorders, and different approaches are described, including percutaneous, which has grown recently. In this modified percutaneous technique, using a guidewire, two portals are ideally made for access to the subtalar joint, regardless of the deformity found in this joint. The technique intents to be faster and decrease morbidity and complication rates. Therefore, the objective of the study was to present a technical variation of the percutaneous technique.